Implications of contextual ambidexterity and digital platform capability on SME performance: the role of absorptive capacity as a moderator - Ramdan, Mohamad Rohieszan; Abdullah, Nor Liza; Abd Aziz, Nurul Ashykin; Mohd Fuzi, Nursyazwani; Ong, Sharon Yong Yee; Ab Wahab, Nur Yuhainis (Penerbit Universiti Kebangsaan Malaysia, 2024)
Contextual ambidexterity and digital platform capability can help SMEs achieve long-term success. However, achieving a balance between exploration and exploitation of contextual ambidexterity for integrating and reconfiguring organisations using digital platform capability is challenging to SMEs. The inherent disadvantage of size and lack of resources plaguing SMEs limits their market competitiveness. In this digital age, it is pertinent for SMEs to focus on capabilities development, especially capabilities that can leverage digital infrastructure to compensate for resource deficiencies. To address this issue, this study examines the implications of contextual ambidexterity and digital platform capability on SMEs performance, and the role of absorptive capacity as a moderator. Using a quantitative method, 157 responses from Malaysian SME managers were analysed using PROCESS Macro. The results show that both contextual ambidexterity and digital platform capability have positive relationships with SME performance, while absorptive capacity positively moderates the relationship between contextual ambidexterity and digital platform capability, enhancing SMEs performance. Overall, this study contributes to the current literature by highlighting contextual ambidexterity and digital platform capabilities as critical dynamic capabilities for SMEs. The findings demonstrate that organisational learning elements represented by absorptive capacity could strengthen the interplay of dynamic capabilities to achieve the competitive advantage. This study can also help SME managers in developing countries to develop strategic actions to achieve superior performance through continuous and sustainable learning, as well as provide some suggestions for future research.